Large scale MHD properties of interplanetary magnetic clouds - Dasso, Sergio Ricardo (2005)
Magnetic Clouds (MCs) are the interplanetary manifestation of Coronal Mass Ejections. These huge astrophysical objects travel from the Sun toward the external heliosphere and can reach the Earth environment. Depending on their magnetic field orientation, they can trigger intense geomagnetic storms. The details of the magnetic configuration of clouds and the typical values of their magnetohydrodynamic magnitudes are not yet well known. One of the most important magnetohydrodynamic quantities in MCs is the magnetic helicity. The helicity quantifies several aspects of a given magnetic structure, such as the twist, kink, number of knots between magnetic field lines, linking between magnetic flux tubes, etc. The helicity is approximately conserved in the solar atmosphere and the heliosphere, and it is very useful to link solar phenomena with their interplanetary counterpart. Since a magnetic cloud carries an important amount of helicity when it is ejected from the solar corona, estimations of the helicity content in clouds can help us to understand its evolution and its coronal origin. In situ observations of magnetic clouds at one astronomical unit are in agreement with a local helical magnetic structure. However, since spacecrafts only register data along a unique direction, several aspects of the global configuration of clouds cannot be observed. In this paper, we review the general properties of magnetic clouds and different models for their magnetic structure at one astronomical unit. We describe the corresponding techniques to analyze in situ measurements. We also quantify their magnetic helicity and compare it with the release of helicity in their solar source for some of the analyzed cases.